Tanks & military vehicles 300 of the world's greatest military vehicles - Trewhitt, Philip (Amber Books, 2016)
Explore every major tank from World War I to the present day. From the crude, unreliable tanks that first appeared on the Western Front during World War I to today's high-tech machines, these are the 300 most important. Arranged by type from main battle tanks and tank destroyers to armored cars, amphibious vehicles, and anti-aircraft guns, the examples here include the Mark V Male, Tiger, Sherman, and T-34 on up to the M1 Abrams, Challenger, and Warrior. Each vehicle receives a full-page entry featuring a color side-profile illustration; a detailed specifications table with country of origin, crew, weight, dimensions, armor, armament, powerplant, and performance; and a summary of the tank's development and service history.